Species specialization limits movement ability and shapes ecological networks: the case study of 2 forest mammals. Issue 3 (18th July 2018) - Dondina, Olivia; Orioli, Valerio; Chiatante, Gianpasquale; Meriggi, Alberto; Bani, Luciano
Abstract: To counteract the negative effects of forest fragmentation on wildlife, it is crucial to maintain functional ecological networks. We identified the ecological networks for 2 mammals with very different degrees of forest specialization, the European badger Meles meles and the Roe deer Capreolus capreolus, by differentiating 4 agroforestry elements as either nodes or connectivity elements, and by defining the distance that provides the functional connectivity between fragments. Species occurrence data were collected in a wide agroecosystem in northern Italy. To test the role of hedgerows, traditional poplar cultivations, short rotation coppices, and reforestations as ecological network elements for the 2 species we applied the method of simulated species perceptions of the landscape (SSPL), comparing the ability of different SSPLs to explain the observed species distribution. All analyses were repeated considering different scenarios of species movement ability through the matrix. Model outputs seem to show that the specialist and highly mobile Roe deer has the same movement ability throughout the matrix (2 km) as the European badger, a smaller, but generalist species. The ecological network identified for the European badger was widespread throughout the area and was composed of woodlands, poplar cultivations and hedgerows as nodes and short rotation coppices as connectivity elements. Conversely, the ecological network of the Roe deer was mostly limited to the main forest areas and was composed of woodlands, poplar cultivations and reforestations as nodes and short rotation coppices and hedgerows as connectivity elements. The degree of forest specialization strongly affects both species perception of habitat and movement ability throughout the matrix, regardless of species size. This has important implications for species conservation.